Pharmacological and phosphoproteomic approaches to roles of protein kinase C in kappa opioid receptor-mediated effects in mice. (15th December 2020) - Liu, Jeffrey J.; Chiu, Yi-Ting; Chen, Chongguang; Huang, Peng; Mann, Matthias; Liu-Chen, Lee-Yuan
Abstract: Kappa opioid receptor (KOR) agonists possess adverse dysphoric and psychotomimetic effects, thus limiting their applications as non-addictive anti-pruritic and analgesic agents. Here, we showed that protein kinase C (PKC) inhibition preserved the beneficial antinociceptive and antipruritic effects of KOR agonists, but attenuated the adverse condition placed aversion (CPA), sedation, and motor incoordination in mice. Using a large-scale mass spectrometry-based phosphoproteomics of KOR-mediated signaling in the mouse brain, we observed PKC-dependent modulation of G protein-coupled receptor kinases and Wnt pathways at 5 min; stress signaling, cytoskeleton, mTOR signaling and receptor phosphorylation, including cannabinoid receptor CB1 at 30 min. We further demonstrated that inhibition of CB1 attenuated KOR-mediated CPA. Our results demonstrated the feasibility of in vivo biochemical dissection of signaling pathways that lead to side effects. Highlights: PKC participates in κ opioid receptor-mediated behavior responses and signaling in brains. PKC regulated GRK5/6 and Wnt signaling at early time for KOR activation. PKC mediated mTOR pathways and CB1 at the late time for KOR activation. CB1 is involved in U50, 488H-induced aversion effect in a PKC-dependent manner.